Study the process of producing methane gas (CH4) used for industrial purposes using the method (Biogas) - Hadi, Araa Ali; Mahdi, Noor Mahmood (Technium: Romanian Journal of Applied Sciences and Technology, 2024)
The methane gas (CH4) production includes many conditions and capabilities, it is useful for industrial purposes, and can be produced in a biological methods called (biogas). This technique depends on the anaerobic fermentation process of organic waste and is carried out by bacteria to give an organic fertilizer that is rich in protein and nitrogen, therefore it is a suitable, promising technology for a triangle (energy, development, and environment). This mixture is a flammable gas resulting from the fermentation of organic matter away from air by anaerobic bacterial microbes resulting in the formation of methane (NH4) at a rate of (75%), and carbon dioxide CO2 by (20%), and the rest the ratios are few hydrogen (H2), nitrogen (N2), and hydrogen sulfide H2S. And that the methane gas (CH4), which will be a colorless gas, ignites without smoke from it, creating a highly heated blue flame, and is lighter than the air, with a burning temperature of about (700 C ).